The Influence Of Digital Adoption On MSME Performance With Competitor Orientation And Market Orientation As Moderating Variables Among Msmes In The Special Region Of Yogyakarta - Raihan Alfathan Dinatis; Ari Pradhanawati; Ngatno Ngatno (UNIVED Press, 2026)
This study aims to analyze the effect of digital adoption on MSME performance with competitor orientation and market orientation as moderating variables among MSMEs in the Special Region of Yogyakarta. This study uses a quantitative approach with a survey method through questionnaire distribution to MSME owners. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM). The results indicate that digital adoption has a positive and significant effect on MSME performance. Competitor orientation strengthens the effect of digital adoption on MSME performance, although the significance level is moderate. Meanwhile, market orientation shows a negative moderating effect on the relationship between digital adoption and MSME performance. The study also finds that competitor orientation and market orientation do not directly affect MSME performance. The findings suggest that digital transformation has become a dominant factor in improving MSME performance compared to traditional market orientation. Therefore, MSMEs need to strengthen their digital capabilities to remain competitive in a dynamic business environment.